Technology education at the beginning and during school reform in Slovakia - BÁNESZ, Gabriel (Journal of Education, Technology and Computer Science, 2013)
The article presents the aims and objectives of the KEGA project: Analysisof the reform’s impact on technology education in elementary schools. In thecontribution, the author presents results of research, which focused on surveys ofthe state of technology education in elementary schools at the time of the schoolreform’s introduction. These results will form the basis for comparison of thestate of technology education at the beginning of the reform and now.